MOLECULAR EPIDEMIOLOGICAL ANALYSIS OF HIV INFECTION IN NORTHERN SEAPORTS OF RUSSIA - E. V. Kazennova; V. Yu. Laga; K. B. Gromov; M. N. Sankov; E. S. Popova; E. G. Lgumnova; E. N. Oparina; T. A. Sorokina; M. R. Bobkova (Problems of Virology, 2017)
The results of the molecular-epidemiological analysis of HIV-1 variants circulating in Arkhangelsk and Murmansk - northern seaports of Russia - were presented. In these seaports the HIV-1 variants belonging to subtype A1 were predominant (93% in Murmansk, 83% in Arkhangelsk). In addition to these variants, viruses of other subtypes such as B, C, D and recombinant forms CRF02_AG and CRF03_AB were identified. The heterogeneity of circulating HIV-1 variants was higher in Arkhangelsk than in Murmansk. According to the results of phylogenetic analysis, subtype A1 sequences formed the common branch with nucleotide sequences of IDU-A strains found in other regions of Russia. HIV-1 variants of subtype B sub-clustered with sequences of East European B-variants. The recombinant strains CRF02_AG formed the common branch with HIV-1 sequences from Central Asia republics of the former USSR. Among 124 therapy-naive patients from Arkhangelsk and Murmansk (n = 124) the transmitted resistance was less than 5%.